THE EFFECT OF CAREER DEVELOPMENT AND JOB CHARACTERISTICS ON EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT - Hana Novie Eva Shinta; Lie Liana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effect of career development and job characteristics on employee performance mediated by organizational commitment. This study uses a quantitative approach with a population of 58 employees of the Wonosobo District BPPKAD. The data were processed using SPSS version 26 software. Data analysis techniques included respondent description, variable description, validity test, reliability test, F test, coefficient of determination (R2) test, t test, and Sobel Test. The results showed that career development had a positive effect on organizational commitment, job characteristics had a positive effect on organizational commitment, career development has a positive effect on employee performance, job characteristics have a positive effect on employee performance, organizational commitment has a positive effect on performance, organizational commitment mediates the effect of career development on employee performance, and organizational commitment mediates the effect of job characteristics on employee performance.